Healthcare Sector Service Quality & Residents’ Satisfaction in Ajman, as a Model for Emerging Countries - Al Hubaishi, Hajar (Advances in Social Sciences Research Journal, 2026)
The purpose of this paper is to identify Ajman residents’ satisfaction on healthcare service. The proposed measurement for Ajman Residents’ Satisfaction was tested using data collected from the three areas of Ajman, namely Ajman City, Masfout, and Manama. A total of 95,531 households[1] are living in the Emirate of Ajman. Out of these 1,167 households’ responses were collected. About were United Arab Emirates (UAE) nationals and about 51.4% were foreign nationals. All of them were permanently residing in the Emirate of Ajman and has prior experience in availing any healthcare service in the same emirate. Data were analyzed using Microsoft Excel, the Statistical Package for the Social Sciences (SPSS) version 22. Findings show that in the government sector only tangible and empathy correlate positively with healthcare service quality, which also had a strong positive correlation with residents’ satisfaction, while reliability, assurance and responsiveness were not sufficiently correlated to healthcare service quality. On the other hand, for the private sector, except for responsiveness, assurance and tangible dimensions, reliability and empathy correlate positively with healthcare service quality, which also had a strong, positive correlation with residents’ satisfaction